(untitled) (Research, Society and Development, 2020)
The goal of this study was to analyze the influence that working from home had on the informal conversations, during the COVID-19 pandemic, in organizations. By means of online asynchronous interviewing, 40 employees and professionals who, due to the pandemic, started working from home had their answers evaluated by content analysis. The results showed that the majority of participants started using digital communication and information technologies, such as remote communication apps and mobile devices, in order to have informal conversations. However, there was a decrease in the frequency of those conversations for many participants, and in some other cases, conversations ceased completely. Considering, on one hand, the positive effects of informal conversations on work and integration, and on the other, the possible increase of physical and social isolation caused by working from home during the pandemic, the results suggest potential negative impacts on the efficiency of the work performed, as well as on the quality of life and wellbeing on the work environment. From the theoretical perspective, the investigation aids the unveiling of the effects that working from home has on informal communications in intense physical and social isolation conditions. From a practical perspective, this comprehension can help organizations and their managers to consider the aspect of informal conversations when implementing their telecommuting processes. This implies the consideration of the adoption of practices which value direct interactions, such as business meetings and periodic informal face-to-face moments, as well as increasing the possibility of more significant online communications.